SYNTHESIS AND ANALYSIS OF SOME N-AROMATIC DERIVATIVES OF 4- OXOPYRIMIDINE - T. Yu. Archinova; I. P. Kodonidi; E. A. Maslovskaya (Фармация и фармакология (Пятигорск))
We have carried out preliminary analysis of foreseeable biological activity of some compounds derivants of 4-oxopyrimidine with a use of PASS program. We have established that they should have anti-inflammatory, benzothiazepine, analgesic, hypotensive, nootropic activity.Molecular docking method (Autodock 4.0) allowed modeling of interaction of 4-oxopyrimidine derivatives with GABA, dopamine and benzothiazepine receptors. On the basis of the data received we forecasted structures of N-aromatic derivatives of 4-oxopyrimidine. The derivatives of 4-xopyrimidine we received with a reaction of cyclocondensation of N-acyl-β-ketamides with aromatic amines. We have synthesized five compounds. Using IR, UV and NMR spectrometry we have established its presumable structure as well as some physical and optical parameters. We have elaborated methods of quantitative spectrophotometric determination of two synthesized compounds and made its validation estimation.